The main influencing factors of soil mechanical characteristics of the gravity erosion environment in the dry-hot valley of Jinsha river - Zhao, Yangyi; Duan, Xu; Han, Jiaojiao; Yang, Kun; Xue, Yang (Open Chemistry, 2018)
The dry-hot valley region counts as one of the most eco-sensitive zones in China, the issue of soil erosion is critical in regional ecological environment, soil mechanical property is one of the primary factors confining the occurrence of erosion, and it is attached crucial significance to in ascertaining the characteristics and principal factors of soil mechanics, and how to prevent and control soil erosion in arid red soil area of dry-hot valley. Through monitoring field location and directly shearing, the soil mechanical characteristics and the primary influencing factors of the mass erosion environment in the basin were ascertained. As the result indicates: (1) The soil moisture content, cohesion and internal friction angle are evidently correlated with each other abiding by power function, the relationship among soil cohesion, internal friction angle and volume moisture content goes as: (2) The soil being large in pore radius vary in number and distribution evidently with structure and destruction degree ( <0.05). Soil aggregation was also significantly different (P<0.05), with the increasing of structural failure rate, the shear strength of soil decreased, and the probability of damage was increased as the external load increaseing. (3) The disintegration of soil can be effectively decelerated, and anti-disintegration ability of soil can be enhanced by the root system. The impact exerted by plant root system on shear strength of soil decreased as soil got deeper, more than a certain depth can be ignored; the impact exerted by plant root system on small-scale gravitational erosion was particularly evident, whereas the impact exerted by large-scale mass erosion was comparatively small. The ability of plant roots to optimize soil resistance was primarily through the roots shorter than 2 mm, the effective fibrous roots in the soil of the Benth and the were comparatively small, and the root of the herbaceous plants was comparatively large.